Menindak Degradasi Bermedia Sosial Dalam Perspektif Jean Paul Sartre - Kristia Agung Pratama; Esteria Tatubeket; Hendrik Zulfan Gori; Amsal Amsal (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
The fundamental problem is when awareness has been reduced by social media activities which take away that awareness. As a result, awareness experiences alienation and falls into a hole that is shackled on social media. The aim of this research is to awaken reduced consciousness so that it can be responsible for existential freedom; and take responsibility for others. In this research, researchers used a literature study method which was then compiled into a written framework. Applicatively, when you realize freedom, then act on the basis of awareness, then the action will be realized on the basis of awareness. On the contrary, consciousness that has been reduced tends to polarize which reduces consciousness, so that awareness is not maximized in being responsible for one's free will.